2021
DOI: 10.1099/mic.0.001002
|View full text |Cite
|
Sign up to set email alerts
|

The putative phosphate transporter PitB (PP1373) is involved in tellurite uptake in Pseudomonas putida KT2440

Abstract: Tellurium oxyanions are chemical species of great toxicity and their presence in the environment has increased because of mining industries and photovoltaic and electronic waste. Recovery strategies for this metalloid that are based on micro-organisms are of interest, but further studies of the transport systems and enzymes responsible for implementing tellurium transformations are required because many mechanisms remain unknown. Here, we investigated the involvement in tellurite uptake of the putative phospha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…3 , 5 ). Prior to this research, references to the native Pi transport system of P. putida KT2440 were scarce [ 45 , 46 ], and most annotations of transporters were based on their homology with their E. coli ’s counterparts. During this study, we found that deletions in what we identified by homology as PitA ( PP_4103 ) did not dramatically affect the growth of P. putida in Pi (Additional file 1 : Figure S2A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 , 5 ). Prior to this research, references to the native Pi transport system of P. putida KT2440 were scarce [ 45 , 46 ], and most annotations of transporters were based on their homology with their E. coli ’s counterparts. During this study, we found that deletions in what we identified by homology as PitA ( PP_4103 ) did not dramatically affect the growth of P. putida in Pi (Additional file 1 : Figure S2A).…”
Section: Discussionmentioning
confidence: 99%
“…As such, its regained ability to grow on P sources is most likely resulting from a series of acquired evolutionary mutations. Since our modifications have not affected the core Pi metabolism of the mutant but only its transport, we believe that these mutations may have altered the structural configuration of other native transporters specific to molecules such as sulphate (similar in size to phosphate), or promiscuous transporters with the ability to cotransport different molecules [ 46 ]. As a result, these mutations could either unlock new transport abilities or improve the specificity of a low affinity transporter to incorporate Pi.…”
Section: Discussionmentioning
confidence: 99%
“…For mutant complementation the protocol described by Montenegro et al ( 2021 ) was used. Briefly the DNA sequence encoding the respective gene for each mutant (see Table 1 ) of P. putida KT2440 was amplified directly from the chromosome of the bacterium with their corresponding primers (see Table S3 ).…”
Section: Methodsmentioning
confidence: 99%
“…This metabolic capacity could be used for the implementation of reduction reactions such as the transformation of oxyanions (e.g. selenite, tellurite) to their respective elemental species (Se 0 , Te 0 ) (Montenegro et al, 2021 ; Vieto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The soil bacterium Pseudomonas putida KT2440 is known to use the later route to detoxify tellurite, forming a black precipitate inside the cells. In this paper Rafael Montenegro ( @RafaMM19 ), Sofía Vieto ( @sofivieto ) and colleagues from the group of Max Chavarría ( @MaxChavarriaV ), at the Centro Nacional de Innovaciones Biotecnológicas (CENIBiot), Costa Rica, have investigated how the tellurite enters the cell and identified one of the transporters involved [ 6 ]. They studied the P. putida orthologue of an inorganic phosphate transporter, PitB, as the Escherichia coli PitA protein was known to be involved in tellurite uptake in E. coli [ 7 ].…”
mentioning
confidence: 99%